Influence of light and temperature on seed germination of Cereus pernambucensis Lemaire (Cactaceae) - Socolowski, Fábio; Vieira, Daniela Cristine Mascia [UNESP]; Simão, Edson [UNESP]; Takaki, Massanori [UNESP] (Instituto Virtual da Biodiversidade (BIOTA/FAPESP), 2010)
Este estudo teve como objetivos avaliar os efeitos da luz e da temperatura na germinação de sementes de Cereus pernambucensis, espécie de cacto colunar, nativa do Brasil que ocorre naturalmente na restinga. As sementes foram incubadas sob diferentes isotermas, entre 5 e 45 °C, com intervalos de 5 °C, e sob termoperíodos de 15-20 °C, 15-30 °C, 20-25 °C, 20-30 °C, 20-35 °C, 25-30 °C, 25-35 °C, 30-35 °C, ambos na presença e ausência de luz contínua. As sementes também foram submetidas a um gradiente de fotoequilíbrio do fitocromo a 25 °C. A temperatura ótima para a germinação desta espécie está entre 25 e 30 °C. A alternância de temperatura não alterou a porcentagem de sementes germinadas, porém observaram-se alterações na velocidade e índice de sincronização. As sementes incubadas no escuro não germinaram em qualquer das condições testadas, indicando que a espécie, quando em condições de cultivo, é fotoblástica positiva. As sementes apresentam tolerância a diversas condições de sombreamento, germinando em condições de fluência muito baixa.

The objective of the present study was to evaluate the effects of light and temperature on germination of Cereus pernambucensis seeds, a species of columnar cactus native to Brazil and naturally incident in the restinga. Cereus pernambucensis seeds were incubated under different temperatures, from 5 to 45 °C, with 5 °C intervals, and under alternating temperatures of 15-20 °C, 15-30 °C, 20-25 °C, 20-30 °C, 20-35 °C, 25-30 °C, 25-35 °C, and 30-35 °C, both under continuous white light and dark. The seeds were also incubated in a gradient of phytochrome photoequilibrium at 25 °C. The highest percentage germination in this species was between 25 and 30 °C. The minimum temperature was between 15 and 20 °C and the maximum between 35 and 40 °C. Alternating temperatures did not affect the percentage of seed germination, but it did alter the rate and synchronization indexes. Seeds incubated in the dark did not germinate under any of the conditions tested, indicating that this species when cultivated present light sensitive seeds controlled by phytochrome. The seeds can tolerate a lot of shade conditions, germinating under very low fluence response of phytochrome.
Influência da luz e da temperatura na germinação de sementes de Cereus pernambucensis Lemaire (Cactaceae)
Keywords: cacto colunar; Cereus pernambucensis; restinga; columnar cacti; Cereus pernambucensis; restinga